An Empirical Analysis of Public Debt and Economic Growth: Tunisia as a Case Study - Abdallah, Nizar Ben; Daly, Lamia; Mtir, Imed (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Public debt has resulted in various economic problems in Tunisia since the outbreak of its revolution in 2010. The main objective of study is to examine the impact of public debt on growth in Tunisia during the post-revolution period. This study uses a vector error correction model (VECM) to investigate the impact of public debt on economic growth in Tunisia. The results prove the long-term relationship between all the variables. This study shows the drawbacks of debt and how it hampers economic growth; hence, it has a negative influence on interest rates and investments. This will subsequently lead to an economic recession due to decreasing growth.